Peran Kualitas Laba Terhadap Nilai Perusahaan: Komisaris Independen dan Kualitas Audit sebagai Variabel Pemoderasi - Pauline Arum Diana; Imang Dapit Pamungkas (Jurnal Ekonomi Akuntansi dan Manajemen, 2024)
The company aspires to generate profits so that the firm value becomes high and shareholders can experience prosperity. In achieving this goal, investors typically rely on experienced individuals, such as a commissioner. Investors also tend to trust companies audited by the KAP. This research aims to test and analyze the quality of profits affecting the firm value as well as the audit quality and independent commissioners as a moderation variable. The application used to analyze the data in this study is Warpls 7.0. The population includes all property and real estate companies from 2020 to 2022, with purposive sampling yielding a sample of 122 data over three years. The implications of this research are achieving profits and increasing firm value, placing trust in commissioners, and recognizing the quality of financial reports audited by KAP. The results indicate that quality profits have a stimulating effect on a firm value. Independent commissioners cannot moderate the relationship between the quality of profits and firm value, while audit quality can moderate this relationship. Keywords: Independent Commissioners, Profits, Firm Value, Audit Quality